ERP Subsequent Memory Effects Differ between Inter-Item and Unitization Encoding Tasks - Kamp, Siri-Maria; Bader, Regine; Mecklinger, Axel (Frontiers in Human Neuroscience, 2017)
The “subsequent memory paradigm” is an analysis tool to identify brain activity elicited during episodic encoding that is associated with successful subsequent retrieval. Two commonly observed ERP “subsequent memory effects” (SMEs) are the parietal SME in the P300 time window and the frontal slow wave SME, but to date a clear characterization of the circumstances under which each SME is observed is missing. To test the hypothesis that the parietal SME occurs when aspects of an experience are unitized into a single item representation, while inter-item associative encoding is reflected in the frontal slow wave effect, participants were assigned to one of two conditions that emphasized one of the encoding types under otherwise matched study phases of a recognition memory experiment. Word pairs were presented either in the context of a definition that allowed to combine the word pairs into a new concept (unitization or item encoding) or together with a sentence frame (inter-item encoding). Performance on the recognition test did not differ between the groups. The parietal SME was only found in the definition group, supporting the idea that this SME occurs when the components of an association are integrated in a unitized item representation. An early prefrontal negativity also exhibited an SME only in this group, suggesting that the formation of novel units occurs through interactions of multiple brain areas. The frontal slow wave SME was pronounced in both groups and may thus reflect processes generally involved in encoding of associations. Our results provide evidence for a dissociation of the eliciting conditions of the two types of SMEs and therefore provide a tool for future studies to characterize the different types of episodic encoding.